Residential greenness and reduced depression during COVID-19: Longitudinal evidence from the Canadian Longitudinal Study on Aging. - Paul J Villeneuve; Susanna Abraham Cottagiri; Ying Jiang; Margaret De Groh; Esme Fuller-Thomson (PLoS ONE)
Urban greenness has several demonstrated mental health benefits, including lower rates of depression and loneliness. Few studies have evaluated the possible benefits of greenness on depression during the COVID-19 worldwide pandemic. We investigated this topic using a prospective cohort of Canadian adults. Our study population consisted of 13,130 participants, 50 years of age and older, of the Canadian Longitudinal Study on Aging. The Center for Epidemiological Studies Depression Short Scale (CES-D-10) screening tool was used to determine whether individuals had depression at two-time points (pre-pandemic, and 6 months into the pandemic). Greenness was characterized using the maximum annual mean Normalized Difference Vegetation Index (NDVI) (500m buffer) from the pre-pandemic residential address. Logistic regression was used to estimate the odds of depression during the pandemic in relation to an interquartile range increase in the NDVI. The prevalence of depression increased nearly twofold between the pre-pandemic and pandemic surveys (8.5% to 16.5% for men; 14.4% to 27.1% for women). Irrespective of depression status before the pandemic, those with higher residential greenness had lower odds of depression during the pandemic. Among those 'not depressed' pre-pandemic, the odds ratio (OR) of depression during the pandemic in relation to an interquartile increase in the NDVI (0.06) was 0.91 (95% CI: 0.85-0.97), while a weaker association was found for those depressed pre-pandemic (OR=0.96; 95% CI: 0.83-1.11). The inverse association between greenness and depression during the pandemic was strongest among those of lower socioeconomic status. Our findings suggest that green spaces in urban areas helped mitigate against depression during the pandemic.